Association of depressive symptoms, physical function, and cardiovascular disease risk in middle-aged and elderly Chinese - Li, Miao; Zhuang, Shuo; Gao, Yan (Frontiers in Medicine, 2025)
ObjectiveCurrent research suggests that depressive symptoms and physical function increase the risk of developing cardiovascular disease (CVD), but how these factors interact to increase the risk of CVD remains unclear. Therefore, we used data from Chinese middle-aged and older adults to investigate the relationship between depressive symptoms and physical function and CVD risk.MethodsUsing information from the China Health and Retirement Longitudinal Study (CHARLS), we examined the relationship between depressive symptoms, physical functioning, and CVD risk in middle-aged and older Chinese adults. The subsequent seven-year endeavor, which ran from 2011 to 2018, enrolled Chinese adults who were middle-aged and older (≥45 years). The exposures of interest were symptoms of depression and physical impairment. To measure depression symptoms, the Center for Epidemiological Studies Depression Scale (CESD-10) was used. The physical disability was ascertained using the physical mobility function. Its principal endpoint was the incidence of CVD. Cox proportional hazards regression methods has been applied to ascertain 95% of the hazard ratios (HRs) and confidence intervals (CIs). Cox multivariate regression and stratified interaction analysis analyses were employed to investigate the association between depressive symptoms, physical functioning, and CVD.ResultsA total of 1980 people were included, of whom the mean age of the participants was 56.4 ± 7.7 years, of whom 1,013 (51.2%) were women. During the maximum follow-up period of 7 years, 303 (15.3%) suffered from cardiovascular disease, of whom 246 (12.4%) had heart disease and 72 (3.6%) suffered from stroke. Compared with those with NDS (no depressive symptoms) (CESD <10) and NPD (no physical dysfunction), those with both DS (depressive symptoms) (CESD ≥10) and PD (physical dysfunction) had the highest risk of overall CVD (adjusted hazard ratio [HR], 1.88; 95% CI 1.18 to 3), coronary heart disease (HR, 2.45; 95% CI 1.44 to 4.18) and stroke (HR, 0.45; 95% CI 0.15 to 1.31), which were most common in people aged 60 years or younger.ConclusionThis study found that older adults with DS and PD were strongly associated with an increased risk of CVD.